Type-3 Hyaluronan Synthase Attenuates Tumor Cells Invasion in Human Mammary Parenchymal Tissues - Wen-Jui Lee (MDPI AG, 2021)
The microenvironment for tumor growth and developing metastasis should be essential. This study demonstrated that the hyaluronic acid synthase 3 (HAS3) protein and its enzymatic product hyaluronic acid (HA) encompassed in the subcutaneous extracellular matrix can attenuate the invasion of human breast tumor cells. Decreased HA levels in subcutaneous Has3-KO mouse tissues promoted orthotopic breast cancer (E0771) cell-derived allograft tumor growth. MDA-MB-231 cells premixed with higher concentration HA attenuate tumor growth in xenografted nude mice. Human patient-derived xenotransplantation (PDX) experiments found that HA selected the highly migratory breast cancer cells with CD44 expression accumulated in the tumor/stroma junction. In conclusion, HAS3 and HA were detected in the stroma breast tissues at a high level attenuates effects for induced breast cancer cell death, and inhibit the cancer cells invasion at the initial stage. However, the highly migratory cancer cells were resistant to the HA-mediated effects with unknown mechanisms.